Orlando; a biography. - Woolf, Virginia, 1882-1941 (Harvest book, 1973)
Orlando is destined to live for four hundred years. During the Elizabethan era, the young courtier Orlando becomes a lover to the aging Queen and embarks on an intense affair with the beautiful Russian Princess Sasha. Yet while Orlando can fulfil most of his desires, he never quite seems to fit in. Then one night, Orlando falls into a deep sleep and awakes transformed, emerging as a woman in eighteenth-century London.